Prevalência das más oclusões em crianças na clínica de graduação da Faculdade de Odontologia de Araraquara - UNESP - Monini, André da Costa [UNESP]; Amaral, Roberta Maria de Paula [UNESP]; Gandini, Márcia Regina Elisa Aparecida Schiavon; Gandini Júnior, Luiz Gonzaga [UNESP] (My University, 2010)
The aim of this study was to evaluate in dental models the occlusal relationship of children treated or in orthodontic treatment of the Undergraduate Clinic of Araraquara Dental School – UNESP. It was analyzed the vertical, anteroposterior and transversal relationships of the casts models of 388 children by two previous calibrated examiners. The results were analyzed by descriptive statistics and it was found higher prevalence of occlusal deviations in the vertical direction, followed by the sagital dimension and in lower prevalence of the transverse direction.

Este trabalho teve por objetivo avaliar em modelos de gesso as relações oclusais de crianças tratadas ou em tratamento ortodôntico na Clínica de Graduação da Faculdade de Odontologia de Araraquara - UNESP. Foram analisadas as relações verticais, ântero-posteriores e transversais dos modelos de estudo de 388 crianças por dois examinadores previamente calibrados. Os resultados foram analisados por meio de estatística descritiva e identificou-se maior prevalência de desvios da oclusão no sentido vertical seguido pelo desvio no sentido sagital e em menor prevalência no sentido transversal.
Prevalence of malocclusions in children in the graduate clinic of Araraquara College of Dentistry
Keywords: Malocclusion; Prevalence; Orthodontics; Má oclusão; Prevalência; Ortodontia